KORELASI ANTARA PROFIL HEMATOLOGI DENGAN PROCALCITONIN PADA PASIEN TERKONFIRMASI COVID-19 - puspitasari Puspitasari; Andika Aliviameita; Evi Rinata; Dira Nadila (Universitas Muhammadiyah Surabaya, 2021)
Covid-19 is an infectious disease caused by SARS-CoV 2 and has spread very quickly. Several laboratory examinations were carried out on Covid-19 patients including molecular examinations, hematological profiles, and serology. This study aims to determine the relationship between leucocyte, d-dimer, hemoglobin and thrombocyte against procalcitonin in patients with Covid-19. This was an observational analytic study with cross sectional design. A sample of 50 was taken selectively at Aisyiyah Siti Fatimah Tulangan Hospital in November 2020 - January 2021. Multiple linear regression test results showed relationship between leucocyte with procalcitonin (b = -0.64; p = 0.426), d-dimer with procalcitonin (b = 2.702; p = 0.010), hemoglobin with procalcitonin (b = 0.656; p = 0.255), and thrombocyte with procalcitonin (b = 0.037; p = 0.002) . Based on the results, it is found that there is relationship between leucocyte, d-dimer, hemoglobin, and thrombocyte againts procalcitonin in Covid-19 patients.